2017
DOI: 10.22374/1710-6222.24.3.4
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Midodrine for Hypotension Outside of the Intensive Care Unit

Abstract: Midodrine is an oral, peripherally acting alpha-adrenergic agonist. After gaining Food and Drug Administration (FDA) approval in 1996 for orthostatic hypotension, its use has evolved to target vasoplegic conditions such as intradialytic hypotension in the end-stage renal disease population, refractory ascites in cirrhotic patients to support diuresis, and in hepatorenal syndrome. Upon oral ingestion, the drug undergoes enzymatic hydrolysis to an active metabolite, desglymidodrine. Its use has been well tolerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Common adverse events are supine hypertension, piloerection, and scalp pruritus. 76 Screening for hypovolaemia is important as midodrine is not effective when plasma volume is reduced. Caution should be exercised in patients with renal failure or urinary retention.…”
Section: Discussionmentioning
confidence: 99%
“…Common adverse events are supine hypertension, piloerection, and scalp pruritus. 76 Screening for hypovolaemia is important as midodrine is not effective when plasma volume is reduced. Caution should be exercised in patients with renal failure or urinary retention.…”
Section: Discussionmentioning
confidence: 99%
“…Midodrine is an oral alpha agonist that is currently indicated in patients with orthostatic hypotension, intradialytic hypotension and blood pressure management in cirrhosis and hepatorenal syndrome. [7][8][9][10][11][12] Prior work has assessed midodrine efficacy in critically ill patients with mixed results. Earlier trials have demonstrated reduced duration of intravenous vasopressor therapy and a decreased ICU LoS with midodrine therapy.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Midodrine is an oral alpha agonist that is currently indicated in patients with orthostatic hypotension, intradialytic hypotension and blood pressure management in cirrhosis and hepatorenal syndrome 7–12. Prior work has assessed midodrine efficacy in critically ill patients with mixed results.…”
Section: Introductionmentioning
confidence: 99%
“…Midodrine (a vasoconstrictor and αSNS-agonist) has been used for patients with low BP and HR with reduced EF (HFrEF), who have been precluded from instituting β-blockers and renin-angiotensin system blockers. Midodrine raises BP so patients may tolerate conventional pharmacological therapy [ 19 ].…”
Section: Pharmacological Therapymentioning
confidence: 99%